Company’s Return After Initial Public Offering (ipo) Case Study- Saidal- - Labed, Rima (جامعة الوادي - University of Eloued, 2022)
The present research paper aims to identify and analyze SAIDAL’s return ratios, as well as to make a comparison between these crucial elements in the estimation of the company’s financial performance for two periods: the first concerns the period prior IPO, and the second one concerns the period post IPO.c An Initial Public Offering, could bring numerous benefits to the company, such as better awareness, lower cost and return improvement. All of that, is confirmed along this study and reflected in its results that show a positive increase in the magnitudes studied, such as the evolution of the investments, the turnover and the net profit over the period 2017- 2019.
مقال
Keywords: Initial Public Offering ; Return ratios ; Economic return (ROA) ; Financial Return (ROE). ; SAIDAL